Important of adequate legislation from the perspective of solid waste management policy / Haidy Henry Dusim, Mohammad Tahir Mapa and Jenny @ Janey Mosikon - Dusim, Haidy Henry; Mapa, Mohammad Tahir; Mosikon, Jenny @ Janey (Universiti Teknologi MARA, Sabah, 2017)
Most studies on sustainable solid waste management issues have been commonly focused on the technical perspective although studies also indicated that these issues are also strongly influenced by other aspects such as policy, social, economy, institutional and the environment. The aspect of policy plays an important role towards the sustainability of solid waste management, however studies focusing on analysing the solid waste management from the perspective of policy are still lacking. Therefore, the aim of this paper is to highlight the aspect of policy in the context of solid waste management specifically in the adequacy of the legislation. Previous studies have pointed out that adequate legislation plays an important factor towards influencing the aspect of policy in solid waste management as with the lack of adequate legislation, the policy may not be effective towards achieving sustainable solid waste management. In addition, previous studies may have not clearly explained the meaning of the term adequate legislation and the elements under adequate legislation. Therefore, the purpose of this paper is to explore the meaning of adequate legislation and to identify the important elements that make up an adequate legislation. Findings of this study have show that an adequate legislation refers to having comprehensive legislation and specific legislation. This study also discovers that comprehensive legislation and specific legislation is considered as the two important elements under the adequate legislation.